Analysis of Long-Term Cochlear Implantation Outcomes and Correlation With Imaging Characteristics in Patients With Common Cavity Deformity - Zhang, Lifang; Chen, Biao; Kong, Ying; Liau, Natalia; Wei, Xingmei; Shi, Ying; Chen, Jingyuan; Yang, Mengge; Dhanasingh, Anandhan; Li, Yongxin (Frontiers in Neuroscience, 2022)
Object: To investigate the long-term development of auditory and speech in patients with common cavity deformity (CCD) after cochlear implantation (CI) and its relationship to imaging characteristics. Methods: 23 CCD patients and 59 age- and sex-matched CI children with normal inner ear structure were recruited. The auditory and speech development of these two groups were evaluated at 0, 1, 3, 6, 12, and 18 months after CI activation using four parent reports questionnaires (Categories of Auditory Performance (CAP), Speech Intelligibility Rating (SIR), Meaningful Auditory Integration Scale/Infant-Toddler Meaningful Auditory Integration Scale (MAIS/ITMAIS), and Meaningful Use of Speech Scale (MUSS)). Computed tomography-based 3-dimensional reconstruction of the surgical side of 18 CCD children was performed, the volume and surface area were calculated. Correlation analysis was performed on the imaging performance and postoperative outcomes. Results: The percentages of MAIS/IT-MAIS scores and CAP scores at different evaluation time points are significantly different (p<0.05). When comparing SIR results across time points, significant growth was observed in most of the comparisons. In addition, significant differences (p<0.05) are observed among the percentages of MUSS scores at different time points except the comparison between 0 and 1 month after CI activation. Patients in the CCD group had poorer auditory and speech performances at different stages after CI compared with those in the control group. According to the reconstruction of CCD patients, the volume ranged from 12.21 mm3 to 291.96 mm3; the surface area ranged from 27.81 mm2 to 284.7 mm2. When the lumen surface area was < 190.45 mm2 or the volume was < 157.91 mm3, the survival time for CCD children to achieve a CAP score of 4 after CI was significantly shorter. Conclusion: CI are less effective in CCD patients than in patients with normal inner ear structures, but they can still achieve significant improvement postoperatively. The morphology and size of the inner ear vary in CCD patients, which reflects the degree of inner ear development influences the outcome after CI surgery.